Pulmonary arterial hypertension: challenges and achievements 2021 - E. A. Rezukhina; T. V. Martynyuk; Z. S. Valieva; V. V. Gramovich; I. E. Chazova (Евразийский Кардиологический Журнал, 2022)
Symposium dedicated to pulmonary arterial hypertension took place at the 9th Russian Congress on Pulmonary hypertension on December 14, 2021. In this review key points from Chazova I.E., Martynyuk T.V., Valieva Z.S., Gramovich V.V.`s reports are presented, in which information about PAH treatment goals achievement, COVID-19 pandemic challenges impact on routine clinical practice is demonstrated. In this review current situation in pulmonary arterial hypertension treatment goals and regular risk stratification importance are observed, based on the latest clinical trials combined specific therapy including selective prostacyclin receptor agonist selexipag is demonstrated. special attention is paid to pulmonary hypertension patients’ treatment during COVID-19 pandemic, regular risk stratification necessity is mentioned including remote patient monitoring in order to perform timely escalation in PAH-specific treatment in order to achieve low-risk status and to improve the prognosis of PAH patients.